COVID – 19 case study in emergency medicine preparedness and response: from personal protective equipment to delivery of care (2020)
In late 2019, a novel new virus appeared in China with reports of a cluster of pneumonia cases in the large city of Wuhan. Current epidemiological theories trace the virus's first appearance to a seafood market in the city. It is there the virus was thought to have passed from animals to humans. Hundreds and then thousands of Chinese nationals developed high fevers, body aches, and pneumonia-like symptoms. Testing to determine cause revealed it wasn't SARS, the coronavirus that spread around the country in 2002, or the deadly Middle East Respiratory Syndrome, MERS; nor was it influenza, bird flu, or the adenoviruses that cause respiratory symptoms.49 All this was unfolding just before China's biggest holiday, Spring Festival, a time when hundreds of millions of Chinese travel to celebrate and be with family.20